PENERAPAN TEKNOLOGI SEDERHANA PENJERNIH AIR MODEL BACKWASH PADA WARGA AKCAYA KEMYLA 3 DESA SUI BELIDAK KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA KALIMANTAN BARAT - Gunarto, Gunarto; Julianto, Eko; Zulyan, M.; Iwan, Muhammad; Setiawan, Agus (Universitas Mataram, 2024)
The availability of clean water is a very important basic need for the welfare of the community. Along with the rapid growth in Sungai Kakap District, the demand for clean water continues to increase. However, Sui Belidak Village, especially in the Akcaya Kemyla 3 Complex, has difficulty getting adequate clean water, especially during the dry season. This condition affects the quality of life of local residents and requires solutions to ensure a water supply suitable for consumption for the community. The purpose of this community service is to introduce appropriate technology through a simple water purifier based on backwash filtration as a solution to the problem of clean water in the region. This program will be held at the Akcaya Kemyla 3 Complex from July 11 to 14, 2024. The activities include site surveys, assembly of filter tubes, filling media, installing channel pipes, and assisting residents in using water purifiers based on the backwash system. The results of this activity show a very significant improvement in water quality. Water that was previously cloudy and high in iron has now turned clear, making it suitable for various household purposes such as bathing, washing, and toilet needs. In addition, the community managed to gain a better understanding of the importance of maintaining clean water quality and simple methods to obtain it. It is hoped that the implementation of this water purifier can help people reduce their dependence on the government in terms of providing clean water and directly improve their quality of life.Thus, this program has succeeded in providing real solutions for the residents of Akcaya Kemyla 3 and can be a model for other communities.